Behavioral Treatment of Insomnia: Also Effective for Nocturia. Issue 1 (2nd January 2014) - Tyagi, Shachi; Resnick, Neil M.; Perera, Subashan; Monk, Timothy H.; Hall, Martica H.; Buysse, Daniel J.
<x xml:space="preserve">Abstract</x> Objectives To evaluate changes in self‐reported nocturia in community‐dwelling adults aged 60 and older who received behavioral treatment for chronic insomnia. Design Secondary analysis of a randomized controlled trial of a behavioral intervention for sleep. Setting Academic medical center. Participants Of the 79 enrollees, this analysis focused on 30 who, in addition to insomnia, also reported at least one nightly episode of waking up to void. Intervention The brief behavioral treatment of insomnia (BBTI) group (n = 14) received instructions on reducing time in bed and setting a regular sleep schedule. The information control (IC) group (n = 16) received printed materials. A nurse clinician delivered both interventions. Measurements Self‐reported nocturnal awakenings to void assessed daily for 14 days at baseline and 4 weeks after the intervention. Participants who reported at least one episode of nocturia per night at baseline were included in this analysis. Results In individuals with nocturia at baseline, the total number of nocturnal voids over the 14‐day assessment period decreased by 6.5 ± 4.8 in the BBTI group and increased by 1.3 ± 7.3 in the IC group (P = .04, effect size 0.82). After adjusting for baseline nocturia episodes, the difference remained significant (P = .05). Conclusion In older adults with concurrent insomnia and nocturia, behavioral treatment directed solely at insomnia may also improve self‐reported nocturia. Behavioral treatment of insomnia should be further investigated for its effect on nocturia in individuals with concurrent insomnia and nocturia.